Bioestimulation with Aloe vera L. gel to enhance the growth of sorghum (Sorghum bicolor L. Moench) in Entisols - Araque-Pérez, Joxual Josué (2025)
Introduction. Aloe vera L. is known for its bioactive properties, such as phytohormones and essential amino acids that promote plant development, which may represent an alternative means of harnessing soil elements and making them available to plants. Objective. To evaluate its potential as a biostimulant on the growth of sorghum (Sorghum bicolor L. Moench). Materials and methods. Five seeds were sown per plastic pot, each containing 3 kg of soil (classified as Entisols), using a completely randomized block design with five treatments and three replicates: an absolute control (no treatment), a relative control (conventional fertilization), and three treatments combining different doses of A. vera gel with fertilization (0-46-0 and urea at 100 kg ha-¹). Plant height, shoot dry weight, and root dry weight were analyzed by analysis of variance (ANOVA) followed by Tukey’s test, revealing significant differences (p < 0.05). Results. For biomass variables, treatments with A. vera gel exhibited higher values (shoot dry weight: 3.83 ± 0.55 g; root dry weight: 2.50 ± 0.17 g) compared to the absolute control (shoot: 0.44 ± 0.03 g; root: 0.54 ± 0.03 g) and the relative control (shoot: 1.33 ± 0.15 g; root: 1.27 ± 0.09 g). The same trend was observed for plant height, with treatments containing A. vera gel being significantly greater than the relative control (p < 0.001). Conclusion. The application of 30 to 100 mL of gel per 3 kg of soil, in combination with fertilization, markedly improved sorghum growth, enhancing both shoot and root biomass.